‘Turk Gregory’: Turks and Catholics as Metaphors for Each Other in Shakespeare’s Plays - Haliloğlu, Nagihan (British Institute of Florence, 2014)
[No Abstract Available]
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü